METHODOLOGY OF STEP-BY-STEP TEACHING OF LISTENING COMPREHENSION IN ENGLISH THROUGH INNOVATIVE CLUSTER APPROACH IN PEDAGOGIC EDUCATION - Turaboyeva Khumora (Western European Studies, 2024)
This article explores an effective methodology for enhancing listening comprehension skills in English language learners through a step-by-step teaching framework integrated with an innovative cluster approach. Recognizing the critical role of listening in language acquisition, the article addresses common challenges faced by students and offers a structured method for educators. The proposed methodology consists of three phases: preparation, implementation, and assessment. The preparation phase involves setting clear objectives and selecting appropriate materials tailored to students’ needs. The implementation phase incorporates interactive and collaborative activities that promote engagement and active learning, emphasizing the use of clusters to group related listening tasks. Finally, the assessment phase evaluates student progress through formative assessments, providing feedback for continuous improvement
Keywords: listening comprehension; language acquisition; teaching methodology